ABOUT THE LIFE AND WORK OF IS’HAQXON TO’RA IBRAT, ONE OF THE GREAT REPRESENTATIVES OF THE JADID MOVEMENT - Burkhanova Samira Ravshanbek kizi,; Mirkhakimova Feruza, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation:  This  article  scientifically  analyzes  the  educational  activities, scientific heritage, translation school, printing works and great contribution to Uzbek cultural life of Is’hoqkhon To’ra Ibrat, one of the major figures of the Jadid movement. The study highlights the content of his works such as “History of Ferghana”, Mezon uz-zamon, Lug’ati sitta al-sina, the ideas of enlightenment put forward through them, as well as Ibrat’s role in the process of national awakening at the beginning of the 20th century.